Does Gender Diversity Moderate the Relationship Between Profitability and Company Value ? - M. Muzanni; Indah Yuliana (Faculty of Economics and Business Universitas Jenderal Soedirman, 2021)
This study aims to analyze the influence of profitability on the value of companies with gender diversity as moderation variables whether able to strengthen or only weaken. The population used is property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2017 to 2019. Sampling techniques use purposing sampling as many as 13 companies while hypothesis testing method using descriptive analysis techniques and classical assumption test and moderation regression analysis (MRA) with SPSS program. The results showed that the profitability of Return On Asset (ROA) and Return On Equity (ROE) had a positive and significant effect on the company's value. Gender diversity affects the value of the company and gender diversity is able to strengthen the relationship between profitability and the value of the company. This study supports the signaling theory.